2020
DOI: 10.1016/j.canlet.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR490–3p by H. pylori activates DARPP-32 and induces resistance to gefitinib

Abstract: Infection with Helicobacter pylori (H. pylori) is the main risk factor for gastric carcinogenesis. In this study, we investigated the expression, molecular functions, and downstream effectors of miR490-3p in gastric cancer. We used in vitro and in vivo models to investigate H. pylori in regulating miR490-3p and DARPP-32-dependent functions and therapeutic resistance. Human and mouse neoplastic gastric lesions demonstrated a negative correlation between DARPP-32 and miR490-3p expression (R=−0.58, P<0.01). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Correlation analyses revealed a negative correlation between miR‐490‐3p and ELOA (Figure 7B). Furthermore, recent studies reported that miR‐490‐3p expression is reduced in GC and associated with poor prognosis 18,19 . These results encouraged us to hypothesize that increased expression of ELOA might be attributed to decreased miR‐490‐3p abundance in GC.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Correlation analyses revealed a negative correlation between miR‐490‐3p and ELOA (Figure 7B). Furthermore, recent studies reported that miR‐490‐3p expression is reduced in GC and associated with poor prognosis 18,19 . These results encouraged us to hypothesize that increased expression of ELOA might be attributed to decreased miR‐490‐3p abundance in GC.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, recent studies reported that miR-490-3p expression is reduced in GC and associated with poor prognosis. 18,19 These results encouraged us to hypothesize that increased expression of ELOA might be attributed to decreased miR-490-3p abundance in GC. Luciferase assays confirmed the regulation of ELOA by miR-490-3p both in both HEK293T and AGS suggesting that ELOA is a direct target of miR-490-3p (Figure 7C-E).…”
Section: Eloa Is a Novel Target Of Mir-490-3pmentioning
confidence: 95%
“…At the highest concentration tested (50 µg/ml), both AGN-Pure and AC2 significantly reduced the viability of the A549 cells compared to the control group (0 µg/ml), indicating AGN was effective against lung cancer. AGN acts as an antiprofilating agent by activating the apoptosis pathway that decreases the PI3K/Akt signaling, triggering cancer cell death and preventing lung tumor [18], [46]. Half maximal inhibitory concentration (IC50) was also calculated, indicating the concentration of a flavonoid (AGN) and product AC2 SDSD needed to inhibit the growth of cancer cells by 50%.…”
Section: Anti-proliferative Activitymentioning
confidence: 99%
“…Hypermethylation-mediated silencing of miR-490-3p reactivates SWI/SNF-related, matrixassociated, actin-dependent regulator of chromatin, subfamily d, member 1 (SMARCD1), a chromatin remodeling complex subunit, to impart a malignant phenotype of GC cells [85]. Furthermore, down-regulation of miR490-3p also promotes gefitinib resistance by inducing activation of DARPP-32/PI3K/Akt and STAT3 signaling pathways [86]. Inhibition of miR-210 expression enhances cell proliferation by activating its target stathmin 1 (STMN1) and dimethyladenosine transferase 1 (DIMT1) [87].…”
Section: Helicobacter Pylori-induced Gastric Cancermentioning
confidence: 99%